A Review Established a System for Proposing a Product Halal Certification For Entrepreneurs in Bangkok - kumvilai , Aumpol; Khunintara, Rungcharoen; Seawong, Nitichai; Moohammad, Anussara; Mahamud, Tosaporn; Neramitkanthon, Phitchayut; Shinkoi, Nattalie (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This academic article explores the strategic integration of the halal industry within non-Muslim societies, with a specific focus on Thailand. Despite the significant global growth of the halal market, Thailand faces multifaceted challenges in adopting and embracing this industry, including issues related to social efficiency and a limited understanding of halal support systems. This study utilizes a qualitative methodology, including observations and an analysis of the halal industrial ecosystem, Sharia compliance concepts, and business ecosystem theory. By benchmarking against the Korean halal industry as a case study, the research proposes a systematic framework for entrepreneurs, particularly in the food and beverage sectors. The findings indicate that a comprehensive support system—encompassing clear policies and standardized practices—is essential. In conclusion, developing these systems will enable Thai entrepreneurs to reach their full potential, integrate economic benefits, and mitigate contamination risks within the halal ecosystem. Article history: Received 14 May 2025 Revised 20 July 2025 Accepted 22 July 2025 SIMILARITY INDEX = 0.00 %